2014
DOI: 10.1002/anie.201307989
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Streptolidine Involved Two Unexpected Intermediates Produced by a Dihydroxylase and a Cyclase through Unusual Mechanisms

Abstract: Streptothricin-F (STT-F), one of the early-discovered antibiotics, consists of three components, a β-lysine homopolymer, an aminosugar D-gulosamine, and an unusual bicyclic streptolidine. The biosynthesis of streptolidine is a long-lasting but unresolved puzzle. Herein, a combination of genetic/biochemical/structural approaches was used to unravel this problem. The STT gene cluster was first sequenced from a Streptomyces variant BCRC 12163, wherein two gene products OrfP and OrfR were characterized in vitro to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 33 publications
2
51
0
Order By: Relevance
“…An extract of the active site of OrfP is given in Figure 1 as taken from the 4M2E protein databank (PDB) file [11, 12] . The iron is linked to the protein through interactions with the side chains of His 154 , Glu 156 and His 303 groups in a typical facial 2‐His/1‐Glu triad, which is common for many nonheme iron dioxygenases [13] .…”
Section: Introductionmentioning
confidence: 99%
“…An extract of the active site of OrfP is given in Figure 1 as taken from the 4M2E protein databank (PDB) file [11, 12] . The iron is linked to the protein through interactions with the side chains of His 154 , Glu 156 and His 303 groups in a typical facial 2‐His/1‐Glu triad, which is common for many nonheme iron dioxygenases [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, an arginine guanidino moiety corresponding to the lysine -amino group was surrounded by two acidic residues (D268 and D270 in VioC), suggesting that one or both acidic residues act as substrate acceptors. Subsequent mutagenesis experiments demonstrated that both residues were likely important for activity, but K3H-1 D241 and K4H-4 D253, rather than D243 and E256, respectively, appear to be more critical for the interaction with L-lysine ( 27), daptomycin-type antibiotic (AsnO) (9), and streptolidine (OrfP) (28). On the other hand, L-isoleucine hydroxylase functions as a tricarboxylic acid cycle shunt and in 2-amino-3-methyl-4-ketopentanoic acid biosynthesis, which serves as a metabolic antagonist during vitamin B 12 production (29).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, two research groups reported on genes responsible for biosynthesis of the streptolidine lactam and amino sugar moieties in ST (26,27). The orfP and orfR genes from the ST producer Streptomyces lavendulae BCRC 12163 were found to participate in the early steps of the streptolidine lactam biosynthesis (26).…”
Section: Identification Of the Bd-12-biosynthetic Gene Cluster From Smentioning
confidence: 99%
“…The orfP and orfR genes from the ST producer Streptomyces lavendulae BCRC 12163 were found to participate in the early steps of the streptolidine lactam biosynthesis (26). The stnG, stnI, stnJ, and stnQ genes from the ST producer Streptomyces sp.…”
Section: Identification Of the Bd-12-biosynthetic Gene Cluster From Smentioning
confidence: 99%